DAKWAH PARTISIPATIF PADA FENOMENA PEMBANGUNAN - Fitri Yanti (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2012)
The development of science and technology supports human beings in meeting their needs, and solving the problems they encountered in their daily life. However, on the other hand, people have to be aware of various possible threats that result from this. Participatory approach requires the targets of Islamic preaching involved in the planning of Islamic preaching, even in searching problems and needs. The achieve da'wah success, the effectiveness and efficiency in carrying out Islamic Islamic da'wah should be paid attention and processe through an established da'wah strategy. Development of Islamic da;wah is the intercation of a series religiousity. The equality includes the understanding of Islam completely, religious insight, appreciation and experience. As a process, the basic claim is a change in attitude and behaviour to be oriented towards the source of Islamic values.